Superconvergence results for hypersingular integral equation of first kind by Chebyshev spectral projection methods - Gupta, Saloni; Kayal, Arnab; Mandal, Moumita (Applied mathematics and computation, 2025)
In this article, we propose Chebyshev spectral projection methods to solve the hypersingular integral equation of first kind. The presence of strong singularity in Hadamard sense in the first part of the integral equation makes it challenging to get superconvergence results. To overcome this, we transform the first kind hypersingular integral equation into a second kind integral equation. This is achieved by defining a bounded inverse of the hypersingular integral operator in some suitable Hilbert space. Using iterated Chebyshev spectral Galerkin method on the equivalent second kind integral equation, we obtain improved convergence of O(N−2r), where N is the highest degree of Chebyshev polynomials employed in the approximation space and r is the smoothness of the solution. Further, using commutativity of projection operator and inverse of the hypersingular integral operator, we are able to obtain superconvergence of O(N−3r) and O(N−4r), by Chebyshev spectral multi-Galerkin method (CSMGM) and iterated CSMGM, respectively. Finally, numerical examples are presented to verify our theoretical results. •Developed Chebyshev spectral projection methods for hypersingular integral equations.•Established error bounds and convergence rates for all the proposed methods.•Obtained superconvergence of O(N−4r) using iterated spectral multi-Galerkin method.•Verified theoretical superconvergence results through numerical examples.